Pemeliharaan Peralatan dan Pengawasan Pengolahan Depot Air Minum Isi Ulang dengan Kontaminasi Escherichia coli Pada Air Minum - Ester Saripati Harianja; Apriska Dewi Sipayung; Sri Dearmaita Purba; Tengku Indah Abdilla (Poltekkes Kemenkes Yogyakarta, 2022)
Escherichia coli bacteria found in refilled drinking water shows that the quality of the drinking water does not meet the requirements of drinking water refill depots (DAMIU) set by the government, both in terms of bacteriological examination and human resources. It is probably caused by poor equipment maintenance as well as irregular sanitation and hygiene measure by the owner. According to Permenkes No 492/Menkes/PER/IV/2010, one of the requirements of drinking water is said to be consumable if the total content of Escherichia coli bacteria is 0 per 100 ml. The purpose of this study was to analyze the relationship between equipment maintenance and monitoring of drinking water refill depots with Escherichia Coli contamination in drinking water refill depots in Dolok Masihul District, Serdang Bedagai Regency. This study was an analytical type of research with a cross-sectional design. The population in this study was all DAMIU in Dolok Masihul District, Serdang Bedagai Regency, amounted to 15 DAMIU. By employing a total sampling technique, a total number of 15 DAMIU served as research samples. Based on the results of the Fisher Exact test, it was found that there was a relationship between equipment maintenance and Escherichia coli contamination (p-value = 0.007), and there was a relationship between processing supervision and Escherichia coli contamination in drinking water refill depots in Dolok Masihul District, Serdang Bedagai Regency (p-value = 0.017). It is recommended to the DAMIU manager to complete sanitation facilities and equipment such as closed trash cans, SPAL with a fluent and closed flow, replace gallon brush bristles every 3 months, and carry out regular drinking water quality checks and report to the local Health Office.